Hierarchical assembly of biomass fiber–lamella–macromolecule networks for biocomposites with high strength and water-resistant sealing - Yijin Qiu; Dachuan Zhang; Zhixuan Zhou; Di Yang; Chen Qian; Chaoji Chen; Ze Zhao; Hongbing Deng (Proceedings of the National Academy of Sciences, 2025)
Enhancing mechanical strength and water resistance in cellulose fiber-based materials is crucial for their adoption as sustainable alternatives to petroleum plastics. However, achieving these improvements through a simple, economical, and ecofriendly approach remains a major challenge. Here, we present a chitosan (CS)-driven multiscale assembly and rearrangement strategy that produces fiber–lamella biocomposites with outstanding mechanical strength and water resistance, achieved without any chemical modification, thermal treatments, or mechanical pressing. This method leverages synergetic electrostatic interactions, hydrogen-bonding, and hydrophobic association where negatively charged microscale pliable pollen lamella and positively charged macromolecular CS sequentially assemble within pulp fibers to form dense, water-resistant networks. Relying solely on the spontaneous organization of the three components, the resulting fiber/pollen-CS (FP-CS) biocomposites exhibit superior mechanical strength (~80 MPa) and maintain water stability for up to 100 d. Remarkably, they also enable seamless water-resistant sealing through simple CS application, facilitating ecofriendly production of straws, packaging, and water-resistant patches. This green, scalable, and energy-efficient process uses only biomass feedstocks to produce high-performance biocomposites, offering a promising sustainable alternative to conventional plastics.